Comparison of match-related performance indicators between major professional rugby competitions. Issue 3 (June 2019) - Schoeman, Riaan; Schall, Robert
The study compared performance indicators of four major international rugby union competitions, namely Super Rugby, Aviva Premiership, Guinness Pro 12 and French Top 14. Most performance indicators of Aviva Premiership and Guinness Pro 12 rugby competitions were similar but distinctive from French Top 14 and Super Rugby competitions, which in turn were generally similar. The Aviva Premiership and Guinness Pro 12 had similar numbers of ball carries, tries, offloads, kicks, tackles, line-outs and scrums that were significantly higher than French Top 14 and Super Rugby. Offloads ( p = .0015) and tries ( p = .0368) were significantly higher for Super Rugby than the Guinness Pro 12, but the Guinness Pro 12 had significantly higher counts for carries ( p ≤ .0001), passes ( p = .0010) and kicks ( p = .0054). In contrast, counts of tackle breaks ( p ≤ .0001) and line breaks were significantly higher for Super Rugby in comparison to the Aviva Premiership ( p = .0057), Guinness Pro 12 ( p = .0064) and French Top 14 ( p ≤ .0001). All competitions showed areas of weakness and strength, which could be due to specific game plans followed in the unique pitch and weather conditions during competition.